Effects of green tea and bisphosphonate association on dental socket repair of rats - Mada, Edson Yoshihiro; Santos, Alana Claro Cunha; Fonseca, Angelica Cristina; Biguetti, Claudia Cristina; Neves, Fernando Tozze Alves; Saraiva, Patrícia Pinto; Matsumoto, Mariza Akemi [UNESP] (Elsevier, 2017)
Objectives To evaluate the effects of green tea intake and zoledronic acid intravenous therapy on teeth socket repair. Design Sixty male albinus Wistar rats were divided into 4 groups: C—Control, intravenous (IV) 0.9% saline solution (SS), GT—1% green tea in drinking water and IV SS, BP—IV zoledronic acid (BP), and BP + GT—IV BP and 1% green tea. 0.035 mg/kg of BP was administered every two weeks. After ten weeks, right upper molars were extracted and the green tea started to be offered for GT and BP + GT. After 7, 14, and 28 days the animals were euthanized. Results Histopathology analysis revealed lack of socket repair in BP and BP + GT groups, which presented significant increased number of polimorphonuclear leukocytes at day 28, in comparison with C (p < 0.05). No significant differences were detected between C and the experimental groups at the same period (p < 0.05) when considering mononuclear leukocytes. Immunolabeling revealed that the association of BP and GT caused a slight disturbance in OPG/RANKL system and retarded Runx-2 labeling. Although strong TRAP labeling was observed, most of the positive cells in BP and BP + GT groups were not located on bone surface. Conclusions Socket healing of rats treated with BP and regular drinking green tea presented no relevant differences in comparison to those treated with BP alone.
Keywords: Bisphosphonates; Bone repair; Green tea; Immunohistochemistry; Osteonecrosis; Rats